Predicting collision‐induced dissociation spectra: Semi‐empirical calculations as a rapid and effective tool in software‐aided mass spectral interpretation. (3rd April 2014) - Wright, Patricia; Alex, Alexander; Pullen, Frank
<x xml:space="preserve">Abstract</x> RATIONALE Fifteen molecules were modelled using quantum chemistry, prior to interpreting their collision‐induced dissociation (CID) product ion spectra, in a 'blind trial' to establish if calculated protonation‐induced bond elongation could be used to predict which bonds cleaved during CID. Bond elongation has the potential to be used as a descriptor predicting bond cleavage. METHODS The 15 molecules were modelled with respect to protonation‐induced bond length changes using Density Functional Theory (DFT). Significant bond elongations were highlighted to flag potential bond cleavages. CID product ion spectra, obtained using positive ion electrospray ionisation (Waters Synapt G1), were interpreted to establish if observed bond cleavages correlated with calculated bond elongations. Calculations were also undertaken using AM1 (Austin Model 1) to see if this rapid approach gave similar results to the computationally demanding DFT. RESULTS The AM1‐calculated bond elongations were found to be similar to those generated by DFT. All the polarised bonds observed to cleave (n = 82) had been calculated to elongate significantly. Protonation, possibly via proton migration, on the most electronegative atom in the bond appeared to initiate cleavage, leading to a 100% success rate in predicting the bonds that broke as a result of protonation on a heteroatom. Cleavage of carbon–carbon bonds was not predicted. CONCLUSIONS Cleavage of the polarised bonds appears to result from protonation on the more electronegative atom of the bond, inducing conformational changes leading to bond weakening. AM1‐calculated bond length changes act as a descriptor for predicting bond cleavage. However, the impetus for cleavage of the unpolarised bonds may be product ion stability rather than bond weakening. Copyright © 2014 John Wiley & Sons, Ltd.